2014
DOI: 10.1111/jjns.12059
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a home hazard modification program for reducing falls in urban community‐dwelling older adults: A randomized controlled trial

Abstract: Aim: To evaluate the potential improvement of fall prevention awareness and home modification behaviors and to decrease indoor falls by applying a home hazard modification program (HHMP) in communitydwelling older adults followed up to 1 year in this randomized controlled trial. Methods: The present authors randomly assigned 130 older adults living in the Tokyo metropolitan region to either the HHMP intervention group (n = 67) or the control group (n = 63). Both groups received four, 2 h fall prevention multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 25 publications
2
64
0
2
Order By: Relevance
“…An additional 11 RCTs were identified that were conducted in Asian populations, met the inclusion criteria for the community based falls prevention Cochrane review, and were published after the 2012 Cochrane review (Japan n = 6; [ 43 – 48 ] Taiwan n = 2; [ 49 , 50 ] and China/Hong Kong, [ 51 ] Malaysia [ 52 ] and Singapore [ 53 ] n = 1 each). See Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 11 RCTs were identified that were conducted in Asian populations, met the inclusion criteria for the community based falls prevention Cochrane review, and were published after the 2012 Cochrane review (Japan n = 6; [ 43 – 48 ] Taiwan n = 2; [ 49 , 50 ] and China/Hong Kong, [ 51 ] Malaysia [ 52 ] and Singapore [ 53 ] n = 1 each). See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the Asian studies in the 2012 Cochrane review and subsequent Asian RCTS, the only single intervention types that had more than one randomized controlled trial conducted in Asia were exercise ( n = 15), and environment (home hazard assessment and modification, n = 2 [ 38 , 48 ]). There were also five multiple intervention studies [ 34 , 37 , 41 , 50 , 53 ] (two with two or more single intervention arms included as separate single interventions in the single intervention analyses [ 34 , 37 ]) and four multifactorial intervention studies conducted in Asia [ 35 , 36 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The different examples of lighting interventions that have been studied in the past are: (i) unilateral light paths similar to Gight [21,26,27], (ii) LED strips positioned on and around objects and doors to provide spatial lighting cues [24,32], and (iii) bilateral pathway demarcation with laser lines [33]. Additionally, more awareness should be raised to the importance of appropriate lighting during nightly ambulation, as older people are often unaware of insufficient lighting [34].…”
Section: Further Course Of Action and Areas Of Further Researchmentioning
confidence: 99%
“…19 There was a 12% reduction in falls occurring in the home at 52 weeks. 19 Thus, improved awareness of fall prevention and knowledge regarding home safety requirements are potential factors in reducing the risk of falls.…”
Section: Discussionmentioning
confidence: 95%
“…In a Japanese randomized controlled trial testing an intervention to improve fall prevention for approximately four times (2 h per program), which included educational sessions regarding risk factors for falls, such as food and nutrition, foot self‐care, exercise and home safety practices, using a model mock‐up of a typical Japanese home, was shown to be effective . There was a 12% reduction in falls occurring in the home at 52 weeks . Thus, improved awareness of fall prevention and knowledge regarding home safety requirements are potential factors in reducing the risk of falls.…”
Section: Discussionmentioning
confidence: 99%